Comparison Study between Different Assessment Methods That Applied in Hammurabi College of Medicine - Abdulelah Karbal , Hadeel; Muayad Alfadhel , Samar; M. Al-Mosawi , Hadi; Abid Ali Al-Humairi , Israa; Khalil Ibraheem , Mujtaba; Alaa Hussein , Hussein (Hammurabi Journal of Medical Sciences, 2025)
Background and Objectives: The present study evaluated different assessment methods to assess undergraduate medical students' mental, psychomotor, and coordination skills to ensure their preparedness for future clinical practice. The questions include Multiple Choice Questions, Extended Matching Questions, True/False questions, and Essay. Methods: the present study is designed to be a retrospective cross-section study conducted in Hammurabi College of Medicine by participating in the second and third stages from the first phase throughout the 2023-2024 academic years; the students assessed by different examination formats in the first course used MCQ and short answer assay while in second course the question applied MCQ, EMQ, true &false with the short answer, then a post-test survey format used for each assessment types question included clarity, relevance, fairness and difficulty. Results: the results show that the EMQ and True/False questions in the second semester (S4&S6) FOR the second and third stages improved succeeded significantly P value (0.001 & 0.008) for EMQ and true and false respectively, followed by MCQ as the better-assessed types finally short assay question that provides higher order thinking skills. However, concerns were raised regarding the clarity and difficulty of MCQs and the objectivity of True/False questions. Conclusion: The study highlights the importance of diverse assessment techniques in medical education. EMQs and essay questions were more effective in preparing students for clinical practice, as they align with real-world medical problem-solving. Future research should investigate the long-term correlation between these assessment methods and clinical performance.